Strategi Branding UMKM melalui Pembuatan Katalog Produk Digital untuk Meningkatkan Daya Saing Kedai Tahu Bakso Mama Jo - Azizah, Adinda Riyun; Abimasar, Aang; Pambudi, Agastia Teguh; Ardiansyah, Ahmad Laskar Putra; Taufiqi, Ahmad (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
MSMEs play an important role in the economy, but still face challenges in marketing, especially in the digital era. Kedai Tahu Bakso Mama Jo, as one of the MSMEs, experiences limitations in branding and product promotion strategies. This community service program aims to increase the competitiveness of Kedai Tahu Bakso Mama Jo through the creation of a digital product catalog. The method used is Community-Based Research (CBR), which involves training, mentoring, and implementation of digital catalogs on an online platform. The results of the activity showed that the digital catalog succeeded in increasing product visibility, expanding market reach, and increasing sales by 30% in the first month after implementation. In addition, MSME owners gained skills in digital marketing independently. This program proves that the use of digital technology in branding and marketing can increase the competitiveness of MSMEs sustainably amidst increasingly tight business competition.